Experiencing a Problem-Based Learning Approach for Teaching Reconfigurable Architecture Design - Erwan Fabiani (International Journal of Reconfigurable Computing)
This paper presents the “reconfigurable computing” teaching part of a computer science master course (first year) on parallel architectures. The practical work sessions of this course rely on active pedagogy using problem-based learning, focused on designing a reconfigurable architecture for the implementation of an application class of image processing algorithms. We show how the successive steps of this project permit the student to experiment with several fundamental concepts of reconfigurable computing at different levels. Specific experiments include exploitation of architectural parallelism, dataflow and communicating component-based design, and configurability-specificity tradeoffs.